2020
DOI: 10.1182/blood.2019003140
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against the erythroferrone N-terminal domain prevent hepcidin suppression and ameliorate murine thalassemia

Abstract: Erythroferrone (ERFE) is produced by erythroblasts in response to erythropoietin (EPO) and acts in the liver to prevent hepcidin stimulation by BMP6. Hepcidin suppression allows for the mobilization of iron to the bone marrow for the production of red blood cells. Aberrantly high circulating ERFE in conditions of stress erythropoiesis, such as in patients with β-thalassemia, promotes the tissue iron accumulation that substantially contributes to morbidity in these patients. Here we developed antibodies against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 53 publications
(61 reference statements)
3
41
0
Order By: Relevance
“…Given that osteoblasts secrete ERFE that is known to inhibit hepcidin ( Kautz et al, 2014 ) by sequestering BMPs ( Arezes et al, 2018 ; Wang et al, 2020 ; Arezes et al, 2020 ) that are skeletal anabolics ( Hogan, 1996 ), we measured serum BMP2 concentration to find elevated BMP2 levels in Erfe -/- relative to wild-type mice ( Figure 3A ). Given the specific importance of BMP2 in bone remodeling ( Salazar et al, 2016 ), these results are consistent with the previously demonstrated sequestration of BMP2, along with BMP6, by ERFE ( Wang et al, 2020 )—namely, loss of ERFE led to decreased BMP sequestration.…”
Section: Resultsmentioning
confidence: 99%
“…Given that osteoblasts secrete ERFE that is known to inhibit hepcidin ( Kautz et al, 2014 ) by sequestering BMPs ( Arezes et al, 2018 ; Wang et al, 2020 ; Arezes et al, 2020 ) that are skeletal anabolics ( Hogan, 1996 ), we measured serum BMP2 concentration to find elevated BMP2 levels in Erfe -/- relative to wild-type mice ( Figure 3A ). Given the specific importance of BMP2 in bone remodeling ( Salazar et al, 2016 ), these results are consistent with the previously demonstrated sequestration of BMP2, along with BMP6, by ERFE ( Wang et al, 2020 )—namely, loss of ERFE led to decreased BMP sequestration.…”
Section: Resultsmentioning
confidence: 99%
“…In order to correctly assess ERFE levels in pathologies and after blood donation, appropriate analytical validated quantification of ERFE must be ensured. This will also contribute to correctly evaluate the success of recently suggested anti-ERFE therapies for pathologies with aberrantly high ERFE levels, such as iron-loading anemias [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Compensatory increased erythropoietic activity leads to drastically elevated ERFE levels in both NTDT patients and beta-thalassemic mice, especially due to ongoing ineffective erythropoiesis, which is reflected by the increased levels of GDF15 in patients [ 23 , 41 , 42 ]. Based on this, ERFE is currently being investigated as a potential pharmacological target in NTDT [ 28 , 43 ]. Moreover, the increased erythropoietic drive may lead reticulocytosis and increased sTfR levels [ 40 , 44 ].…”
Section: Regulation Of Iron Overload In Rhamentioning
confidence: 99%